Coated particle material for electrodes of electrochemical cells
By applying a coating containing lithium cations and oxidized sulfur substances on the surface of the cathode active material of an all-solid state battery, the capacity loss and stability problems caused by the incompatibility of the cathode active material with the solid electrolyte are solved, and higher battery performance and stability are achieved.
Patent Information
- Application Number
- CN202380056900.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-27
- Filing Date
- 2023-07-27
- Publication Date
- 2025-03-14
AI Technical Summary
In all-solid state batteries, the cathode active material of the 4V category is incompatible with typical sulfur-containing solid electrolyte materials, resulting in rapid capacity loss and poor long-term stability.
A coating is applied to the surface of the cathode active material, which contains lithium cations and oxidized sulfur substances, which act as a protective layer to prevent the solid electrolyte from being oxidized without inhibiting the transfer of lithium ions.
By using cathode active materials coated with particulate material, capacity loss during circulation of all solid state batteries is reduced and long-term stability is improved.
Smart Images

Figure CN119631193A_ABST
Abstract
Description
[0001] A coated granular material for an electrode of an electrochemical cell and a method for preparing the coated granular material, an electrode comprising the coated granular material, an electrochemical cell comprising the coated granular material, and the use of the coated granular material for preparing an electrode for an electrochemical cell are described.
[0002] High energy density all-solid-state batteries can be achieved by applying + / Li has a cathode active material with a redox potential of 4V or higher (a "4V-class" cathode active material), thereby achieving a high cell voltage. However, such cathode active materials may be incompatible with typical sulfur-containing solid electrolyte materials used in all-solid-state batteries because the cathode active materials may act as oxidants to the solid electrolytes present in the cathode and / or separator layers. The interfacial reaction of the cathode active material with the solid electrolyte containing sulfide or thiophosphate is believed to be one of the main reasons for the rapid capacity loss and poor long-term stability of such all-solid-state batteries.
[0003] The interfacial reactions of common cathode active materials (see below for details) and solid electrolytes containing sulfur (e.g., in the form of sulfides or thiophosphates) can be assigned to (at least) two mechanisms: (i) electrochemical decomposition processes of the solid electrolyte, mainly due to the narrow electrochemical stability window of such compounds, and (ii) degradation processes involving oxygen, which can lead to gas release (e.g., SO 2 The release of oxygen (e.g., release of ions) and leads to the formation of oxidized sulfur species and (in the case of thiophosphate electrolytes) oxidized phosphorus species in the interfacial region. The oxygen source of the latter is the cathode active material itself, leading to structural changes on the surface of the cathode active material (e.g., formation of a rock salt-like phase), which in turn hinders lithium ion transfer between the cathode active material and the solid electrolyte.
[0004] In order to solve this problem, it is proposed to apply a coating to the cathode active material, which coating functions as a protective layer to protect the solid electrolyte from being oxidized by the cathode active material without inhibiting the transfer of lithium ions between the cathode active material and the solid electrolyte.
[0005] Xie et al. (Electrochimica Acta [Electrochemical Journal] 379 (2021) 138124) disclosed that in order to improve nickel-rich LiNi for lithium-ion battery applications 0.8 Co 0.15 Al 0.05 O 2 The cycling stability of the (NCA) cathode material was investigated by the sol-gel method by adding a very small amount of lithium sulfide (Li 2S) as a sulfur-containing additive was used to prepare sulfur-modified NCA cathode materials with bulk and surface co-modification and characterized in comparison with the original NCA material. Physical characterization revealed that during the calcination process, some of the introduced S 2- into the layered oxide lattice to replace oxygen, while some of the introduced S 2- Oxidized to Li coated on the surface of primary nanoparticles of layered oxide 2 SO 4 Thin layer. For convenience, the prepared original NCA and S-modified NCA materials are simply denoted as NCA and S-NCA, respectively. As determined by EDS (energy dispersive X-ray spectrometer) mapping (see Figure 3e), Ni, Co, Al, O and S elements are uniformly distributed in the S-NCA sample.
[0006] US2010 / 0015509 A1 discloses an active material for a battery, comprising lithium titanium composite oxide particles and a coating formed on at least a portion of the surface of the particles, the coating containing at least one element selected from the group consisting of phosphorus and sulfur or a phosphorus compound or a sulfur compound.
[0007] WO 2020 / 249659 A1 discloses a coated granular material used as an electrode active material in an electrode and / or a solid-state lithium-ion electrochemical cell, the coated granular material comprising: a plurality of core particles, each core particle comprising at least one nickel-containing composite layered oxide; and a coating disposed on the surface of the core particles, the coating comprising carbonate ions, lithium and at least one member of the group consisting of aluminum, boron, niobium, phosphorus, silicon, tantalum, titanium, zinc, zirconium and mixtures thereof. WO 2020 / 249659A1 also discloses an electrode for a solid-state or lithium-ion electrochemical cell and a corresponding electrochemical cell, the electrode comprising the coated granular material. The coating comprises carbonate anions, lithium and at least one member of the group consisting of aluminum, boron, niobium, phosphorus, silicon, tantalum, titanium, zinc, zirconium and mixtures thereof.
[0008] However, there is a continuing need to reduce capacity loss during cycling of all-solid-state batteries, and therefore a need for a cathode active material having a coating that acts as a protective layer to protect the solid electrolyte from oxidation by the cathode active material without inhibiting the transfer of lithium ions between the cathode active material and the solid electrolyte. In addition, it is desirable that the coating prevents structural changes in the cathode active material due to interfacial reactions with the solid electrolyte involving oxygen release from the cathode active material.
[0009] According to a first aspect, there is provided a coated particulate material comprising
[0010] C1) a plurality of core particles, each core particle comprising one or more compounds of formula (I):
[0011] Li 1+t [Ni x Co y Mn z M u ] 1-t O 2 (I)
[0012] in
[0013] 0≤x≤1
[0014] 0≤y≤1
[0015] 0≤z≤1
[0016] 0≤u≤0.15
[0017] x+y+z>0
[0018] x+y+z+u=1
[0019] 0≤t≤0.2
[0020] M, if present, is one or more elements selected from the group consisting of Al, Mg, Ba, B and transition metals other than Ni, Co and Mn,
[0021] as well as
[0022] C2) a coating disposed on the surface of the core particles, the coating comprising
[0023] - lithium cations, and
[0024] - Oxidized sulfur species.
[0025] Surprisingly, it has been found that for all-solid-state batteries, when using a cathode active material in the form of a coated granular material according to the first aspect defined above, capacity loss is reduced and long-term stability is improved. The coating (2) of the coated granular material contains oxidized sulfur species, which are inevitably formed by interfacial reactions between the cathode active material and a solid electrolyte containing a sulfide, a halogenated sulfide, a thiophosphate or a halogenated thiophosphate. However, unlike such uncontrolled degradation processes, during the formation of the coated granular material according to the present invention, the reaction is initiated before the cell assembly and allowed to proceed in a controlled manner (for details, see the description of the method for preparing the coated granular material).
[0026] The coating C2) as defined above can help improve the performance of all-solid-state batteries containing solid electrolytes containing sulfides, halogenated sulfides, thiophosphates or halogenated thiophosphates, because the strong reaction tendency of the formation of oxidized sulfur and (if present) phosphorus species at the surface of the cathode active material is well met before the battery cell is assembled and operated. The oxidized sulfur and (if present) phosphorus species (mainly lithium sulfate and lithium phosphate) formed are considered to be stable against further oxidation during the operation of the battery cell. Therefore, it is assumed that during the cycling of the battery cell, structural changes in the cathode active material caused by interfacial reactions involving oxygen release (which is considered to be one of the main reasons for the reduction of battery cell performance during battery cell operation) can be minimized or prevented.
[0027] Compounds of formula (I) are capable of serving as cathode active materials in electrochemical cells. In the context of this disclosure, the electrode of an electrochemical cell that produces a net positive charge when the cell is discharged is referred to as the cathode, and the cathode component that produces said net positive charge by reduction is referred to as the "cathode active material".
[0028] Preferably, each core particle C1) consists of at least one compound of formula (I).
[0029] The preferred cathode active material is Li + / Li have a redox potential of 4 V or higher ("4V class" cathode active materials), thereby enabling high cell voltages. Many such cathode active materials are known in the art.
[0030] Suitable cathode active materials are oxides comprising lithium and one or more members of the group consisting of nickel, cobalt and manganese.
[0031] According to the invention, the cathode active material present in the core particles C1) of the coated particulate material is selected from the group consisting of materials having a composition according to general formula (I)
[0032] Li 1+t [Ni x Co y Mn z M u ] 1-t O 2 (I)
[0033] in
[0034] 0≤x≤1
[0035] 0≤y≤1
[0036] 0≤z≤1
[0037] 0≤u≤0.15
[0038] M, if present, is one or more elements selected from the group consisting of Al, Mg, Ba, B and transition metals other than Ni, Co and Mn,
[0039] x+y+z>0
[0040] x+y+z+u=1
[0041] 0≤t≤0.2.
[0042] In certain cathode active materials according to formula (I), M can be one of Al, Mg, Ti, Mo, Nb, W, and Zr. An exemplary cathode active material of formula (I) is Li 1+t [Ni 0.88 Co 0.08 Al 0.04 ] 1-t O 2 , Li 1+t [Ni 0.905 Co 0.0475 Al 0.0475 ] 1- t O 2 and Li 1+t [Ni 0.91 Co 0.045 Al 0.045 ] 1-t O 2 , where in each case 0≤t≤0.2.
[0043] Suitable cathode active materials are, for example, oxides comprising lithium and one or more members of the group consisting of nickel, cobalt and manganese. These cathode active materials have a composition according to general formula (Ia):
[0044] Li 1+t [Ni x Co y Mn z ] 1-t O 2 (Ia)
[0045] in
[0046] 0≤x≤1
[0047] 0≤y≤1
[0048] 0≤z≤1
[0049] x+y+z=1
[0050] 0≤t≤0.2.
[0051] An exemplary cathode active material according to formula (Ia) is LiCoO 2, Li 1+t [Ni 0.85 Co 0.10 Mn 0.05 ] 1-t O 2 , Li 1+t [Ni 0.87 Co 0.05 Mn 0.08 ] 1-t O 2 , Li 1+t [Ni 0.83 Co 0.12 Mn 0.05 ] 1-t O 2 and Li 1+t [Ni 0.6 Co 0.2 Mn 0.2 ] 1-t O 2 , where in each case 0≤t≤0.2.
[0052] Preferably, the cathode active material according to formula (Ia) is a mixed oxide of lithium with at least one of nickel, cobalt and manganese. More preferably, the cathode active material is a mixed oxide of lithium, nickel, and one or two members of the group consisting of cobalt and manganese.
[0053] Some suitable cathode active materials are mixed oxides comprising
[0054] -lithium,
[0055] - Nickel, and
[0056] -One or two members of the group consisting of cobalt and manganese.
[0057] Exemplary suitable cathode active materials have compositions according to formula (Ib):
[0058] Li 1+t A 1-t O 2 (Ib),
[0059] in
[0060] 0≤t≤0.2
[0061] AContains nickel
[0062] and one or two members of the group consisting of cobalt and manganese,
[0063] and optionally
[0064] - one or more additional transition metals not selected from the group consisting of nickel, cobalt and manganese, wherein the additional transition metals are preferably selected from the group consisting of molybdenum, titanium, tungsten, zirconium,
[0065] - one or more elements selected from the group consisting of aluminum, barium, boron and magnesium,
[0066] wherein at least 50 mol % of the transition metal of A is nickel.
[0067] Suitable cathode active materials having a composition according to formula (Ib) are described, for example, in WO 2020 / 249659 A1.
[0068] The cathode active material having a composition according to general formula (I), especially according to general formula (Ib), may have a layered structure or a spinel structure. In some cases, a cathode active material having a layered structure having a composition according to general formula (Ib) may be preferred, as described in WO 2020 / 249659A1.
[0069] Certain preferred cathode active materials have a composition according to formula (Ic)
[0070] Li 1+t [Ni 1-u-v-w Co u Mn v M w ] 1-t O 2 (Ic)
[0071] in
[0072] M is a member of the group consisting of aluminum, barium, boron, magnesium, molybdenum, titanium, tungsten, zirconium and a mixture of at least two of the foregoing elements, preferably M is or comprises aluminum (most preferably when v is 0),
[0073] 0≤t≤0.2
[0074] 0.04≤u≤0.2
[0075] 0≤v≤0.2, preferably, 0.04≤v≤0.2
[0076] 0≤w≤0.1
[0077] And (u+v+w)≤0.4, and preferably ≤0.3.
[0078] In formula (Ic), the variable "M" may represent any single member of the group of elements as defined above (e.g., "M" may represent tungsten, i.e., "W"), or may represent two or more members of the group of elements as defined above (e.g., "M" may represent the group consisting of aluminum, tungsten, zirconium, and titanium). In the case where "M" represents two or more members of the group of elements as defined above, the superscript (number) "w" accompanying the variable "M" applies to the total number of elements represented by "M" as defined above.
[0079] An exemplary cathode active material of formula (Ic) is Li 1+t [Ni 0.85 Co 0.10 Mn 0.05 ] 1-t O 2 , Li 1+t [Ni 0.87 Co 0.05 Mn 0.08 ] 1-t O 2 , Li 1+t [Ni 0.83 Co 0.12 Mn 0.05 ] 1-t O 2 , Li 1+t [Ni 0.6 Co 0.2 Mn 0.2 ] 1-t O 2 , Li 1+t [Ni 0.88 Co 0.08 Al 0.04 ] 1-t O 2 , Li 1+t [Ni 0.905 Co 0.0475 Al 0.0475 ] 1-t O 2 and Li 1+t [Ni 0.91 Co 0.045 Al 0.045 ] 1-t O 2 , where in each case 0≤t≤0.2.
[0080] In the coated particulate material as described herein, the coating (C2) comprises at least the following ingredients:
[0081] - lithium cations, and
[0082] - Oxidized sulfur species.
[0083] In coating C2), the oxidized sulfur species may be oxidation products of one or more compounds of formula (II)
[0084] (Li 2 S) a (P 2 S 5 ) b (LiX) c (Q 2 / e S) d (II)
[0085] in
[0086] X corresponds to one or more selected from the group consisting of F, Cl, Br and I and pseudohalogen ions,
[0087] Q corresponds to one or more elements selected from the group consisting of metals and metalloids other than Li, wherein Q is preferably selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Z and Mg
[0088] e is the oxidation number of Q
[0089] 0≤a≤1, preferably, 0≤a≤0.98
[0090] 0≤b<1, preferably, 0≤b<0.98
[0091] 0≤c<1, preferably, 0≤c<0.98
[0092] 0≤d<1, preferably, 0≤d<0.98
[0093] a+b+c+d=1
[0094] The premise is that when a=0,
[0095] c>0, preferably ≥0.02
[0096] And one of b and d>0, preferably ≥0.02.
[0097] Preferably, in formula (II), a<1, preferably, a≤0.98.
[0098] Preferably, in formula (II), at least one of b, c and d>0, preferably, at least one of b, c and d>0.02.
[0099] Formula (II) as defined above is interpreted as defining the 2 S.P. 2 S 5 , LiX, and Q 2 / eThe total molar amount of S was normalized to 1. 2 S:P 2 S 5 :LiX:Q 2 / e The molar ratio of S. Formula (II) therefore differs from general formulae in which the molar ratios of the elements (in the present case Li, S, P, X and Q) are usually defined by integer subscripts.
[0100] In formula (II), Q corresponds to one or more elements selected from the group consisting of (i) a metal different from Li and (ii) a metalloid. The term "metal" as used herein includes transition metals. Q is preferably selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg. Within this group, Al, Sn, Zr, Ga, Zn and Mg are metals, while B, Si, Ge and Sb are metalloids. In some cases, Q is selected from the group consisting of (i) a metal different from Li and (ii) B, Si, Be and Sb.
[0101] In formula (II), X corresponds to one or more selected from the group consisting of F, Cl, Br and I and pseudohalogen ions. Preferably, X is Cl.
[0102] As used herein, the term "pseudohalogen anion" means a monovalent anion that is similar to a halogen anion in its chemical properties and can therefore replace a halogen anion in a compound without substantially changing the properties of such compound. The term "pseudohalogen ion" is known in the art, see the IUPAC Gold Book. Examples of pseudohalogen ions are N 3 - 、SCN - , CN - 、OCN - , BF - and BH - In the case where the pseudohalogen ion contains an element from the group consisting of B and / or S, the content of such B or S is not taken into account in the parameters a, b and d of the general formula (II) defined above. Instead, the total amount of halogen ions and pseudohalogen ions is indicated by the parameter "c" of the general formula (II). In the pseudohalogen ion-containing composition of the general formula (II), the pseudohalogen ion is preferably selected from SCN - , BF - and BH - Composed of groups.
[0103] The coating C2) is obtainable by oxidation of the compound of formula (II) as defined above. Thus, the compound of formula (II) as defined above can be used as a precursor for the coating C2) as defined above.
[0104] Preferably, the compound of formula (II) is selected from the group consisting of:
[0105] Lithium sulfide,
[0106] Halogenated lithium sulfide,
[0107] Lithium thiophosphate,
[0108] Lithium halothiophosphate,
[0109] lithium sulfide modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids different from Li,
[0110] a halogenated lithium sulfide modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids different from Li,
[0111] lithium thiophosphate modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids different from Li,
[0112] and a halogenated lithium thiophosphate modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids other than Li.
[0113] When the compound of formula (II) is lithium sulfide, a=1 and b=c=d=0.
[0114] In certain cases it is preferred that the compound of formula (II) is not lithium sulfide.
[0115] When the compound of formula (II) is selected from the group consisting of lithium thiophosphate, c=d=0 and a+b=1.
[0116] When the compound of formula (II) is selected from the group consisting of lithium halogenated sulfides, b=d=0 and a+c=1.
[0117] When the compound of formula (II) is selected from the group consisting of lithium halothiophosphates, d=0 and a+b+c=1.
[0118] When the compound of formula (II) is chosen from the group consisting of lithium sulfides modified with sulfides of one or more elements Q chosen from the group consisting of metals different from Li and metalloids, b=c=0 and a+d=1.
[0119] When the compound of formula (II) is chosen from the group consisting of lithium halogenated sulfides modified with sulfides of one or more elements Q chosen from the group consisting of metals and metalloids different from Li, b=0 and a+c+d=1.
[0120] When the compound of formula (II) is chosen from the group consisting of lithium thiophosphates modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids different from Li, c=0 and a+b+d=1.
[0121] When the compound of formula (II) is selected from the group consisting of lithium halothiophosphates modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids different from Li, a+b+c+d=1.
[0122] Preferred compounds of formula (II) are those selected from the group consisting of thiophosphates and halothiophosphates.
[0123] Preferably, the oxidized sulfur species contain sulfate anions. In the coating C2), the sulfate anions can be detected by X-ray photoelectron spectroscopy (XPS) or by vibrational spectroscopy, i.e. infrared (IR) spectroscopy and Raman spectroscopy. At least a portion of the sulfate anions present in the coating C2), preferably the total amount of sulfate ions present in the coating C2), is present as lithium sulfate Li 2 SO 4 exist.
[0124] In some cases, the coating C2) further comprises an oxidized phosphorus substance. In such a coating C2), the oxidized phosphorus substance may be an oxidation product of one or more compounds of formula (II) as defined above, wherein b>0, preferably, b≥0.02. Thus, such a coating C2) comprising oxidized phosphorus substances is obtainable by oxidizing a compound of formula (II) as defined above, wherein b>0, preferably, b≥0.02. Thus, a compound of formula (II) as defined above (wherein b>0, preferably, b≥0.02) may be used as a precursor of a coating C2) comprising an oxidized phosphorus substance.
[0125] Herein, the compound of formula (II) is preferably selected from the group consisting of:
[0126] The lithium thiophosphate as defined above,
[0127] The lithium halothiophosphate as defined above,
[0128] a lithium thiophosphate as defined above modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids different from Li,
[0129] and a lithium halothiophosphate as defined above modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids other than Li.
[0130] Preferably, the oxidized phosphorus species comprise phosphate anions. In the coating C2), the phosphate anions can be detected by X-ray photoelectron spectroscopy (XPS) or by vibrational spectroscopy, i.e. infrared (IR) spectroscopy and Raman spectroscopy. At least a portion of the phosphate anions present in the coating C2), preferably the total amount of phosphate ions present in the coating C2), is present as lithium sulfate Li 3 PO 4 exist.
[0131] In certain preferred cases, the oxidized sulfur species present in the coating C2) comprise sulfate anions, and the oxidized phosphorus species present in the coating C2) comprise phosphate anions. In the coating C2), the sulfate anions and the phosphate anions can be detected by X-ray photoelectron spectroscopy (XPS) or by vibrational spectroscopy, i.e., infrared (IR) spectroscopy and Raman spectroscopy. At least a portion of the sulfate anions present in the coating C2), preferably the total amount of sulfate ions present in the coating C2), is present as lithium sulfate Li 2 SO 4 and at least a portion of the phosphate anions present in the coating C2), preferably the total amount of phosphate ions present in the coating C2) as lithium sulfate Li 3 PO 4 Therefore, in some cases, the coating C2) contains Li 2 SO 4 and Li 3 PO 4 .
[0132] Known Li 3 PO 4 and Li 2 SO 4 They have moderate ionic conductivity for lithium ions. Therefore, the presence of these compounds on the surface of the cathode active material is not detrimental to the performance of the battery.
[0133] In the coated particulate material as defined above, the fraction of sulfur relative to the total mass of the plurality of core particles C1) and their coating C2) may range from 0.09% to 10.0%, preferably 0.4% to 4.0%, as detected by Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES).
[0134] In some cases, sulfur as detected by inductively coupled plasma optical emission spectroscopy (ICP-OES) may include small amounts of sulfur present in the core particles C1) originating from impurities of the cathode active material. Whether such impurities are present depends on the reactants used to prepare the cathode active material. If present, the sulfur content in the core particles C1) is typically in the range of 0.04 to 0.08 wt.-%, as determined by elemental analysis.
[0135] Preferably, in the core particle C1) of the coated particulate material disclosed herein, the concentration of sulfur is 10% or less, preferably 1% or less, most preferably 0.1% or less of the concentration of sulfur in the coating C2).
[0136] In the coated particulate material as defined above, wherein the coating C2) further comprises oxidized phosphorus species, the fraction of phosphorus relative to the total mass of the plurality of core particles C1) and their coating C2) may be in the range from 0.01% to 10.0%, preferably 0.05% to 4.0%, as detected by inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0137] In certain preferred cases, in the coated particulate material as defined above
[0138] - the fraction of sulfur ranges from 0.09% to 10.0%, preferably from 0.4% to 4.0%, as measured by inductively coupled plasma optical emission spectroscopy,
[0139] as well as
[0140] - the fraction of phosphorus ranges from 0.01% to 10.0%, preferably from 0.05% to 4.0%, as measured by inductively coupled plasma optical emission spectroscopy,
[0141] In each case relative to the total mass of the plurality of core particles C1) and their coating C2).
[0142] In the coated particulate material as defined above, the fraction of sulfate anions relative to the total mass of the plurality of core particles C1) and their coating C2) is preferably in the range from 0.27% to 30.0%, preferably 1.2% to 12.0%.
[0143] In the coated particulate material as defined above, wherein the coating C2) further comprises oxidized phosphorus species, the fraction of phosphate anions relative to the total mass of the plurality of core particles C1) and their coating C2) is preferably in the range from 0.03% to 33.7%, preferably 0.15% to 12.3%.
[0144] In certain preferred cases, in the coated particulate material as defined above
[0145] - the fraction of sulfate anions is in the range from 0.27% to 30.0%, preferably 1.2% to 12.0%
[0146] - the fraction of phosphate anions is in the range from 0.03% to 33.7%, preferably 0.15% to 12.3%
[0147] In each case relative to the total mass of the plurality of core particles C1) and their coating C2).
[0148] In a coated particulate material as defined above, the coating may comprise one or more additional ingredients.
[0149] In some cases, the coating C2) comprises halogen anions. At least a portion of the halogen anions in the coating, preferably the total amount of the halogen anions, is present as lithium halide. In such coating C2), the halogen anions may be derived from one or more compounds of formula (II) as defined above, wherein c>0, preferably c≥0.02. Thus, such coatings C2) comprising halogen anions are obtainable by oxidation of compounds of formula (II) as defined above, wherein c>0, preferably c≥0.02. Thus, compounds of formula (II) as defined above, wherein c>0, preferably ≥0.02, can be used as precursors for coatings C2) comprising halogen anions. The halogen anions are selected from F - , Cl - Br - and I - The group consisting of, preferably Cl - .
[0150] In some cases, the coating (C2) comprises carbonate anions. At least a portion of the carbonate anions in the coating, preferably the total amount of the carbonate anions, are present as lithium carbonate.
[0151] In the coated particle material according to the first aspect described herein, the coating (C2) may contain a total amount of carbonate anions of ≥0.08 mass % relative to the total mass of the multiple (uncoated) core particles (C1). More specifically, the coating (C2) may contain a total amount of carbonate anions in the range of from 0.08 mass % to 1.62 mass %, preferably from 0.12 mass % to 1.22 mass %, and more preferably from 0.16 mass % to 0.81 mass %, relative to the total mass of the multiple (uncoated) core particles (C1) and their coatings (C2). If the content of lithium carbonate in the coating (C2) is too high, the lithium ion conductivity may decrease.
[0152] Without wishing to be bound by any theory, it is currently assumed that the carbonate groups present on the surface of the core particles C1) originate from unavoidable impurities of the cathode active material (impurities may be formed when the cathode active material is prepared or stored in the presence of trace amounts of carbon dioxide and water vapor), and / or in some cases from the use of lithium carbonate as a precursor for synthesizing the cathode active material, and / or from the decomposition of the organic solvent or carrier liquid in the liquid reaction mixture used to prepare the coated particulate material (see below for details) in air or oxygen and reactivity with residual lithium on the particle surface of the cathode active material.
[0153] In the coated particulate material according to the first aspect described herein, at least a portion of the carbonate ions present in the coating (C2) may be present as part of an ionic compound, for example as part of a salt.
[0154] For the purposes of the present disclosure, the amount of carbonate ions present in the coating (C2) can be determined by acid titration combined with mass spectrometry, more preferably according to the method defined in the Examples section of WO 2020 / 249659 A1, performed on a (representative) sample of the coated particulate material.
[0155] In some cases, the coating (C2) comprises anions selected from the group consisting of oxygen anions, hydroxide anions and peroxide anions. At least a portion of the anions in the coating, preferably the total amount of the anions, is in the form of lithium oxide Li 2 O, lithium hydroxide LiOH and lithium peroxide Li 2 O 2 One or more of them exist.
[0156] In certain specific cases, the coating C2) comprises oxyanions of elements from the group consisting of metals and metalloids other than Li. The term "metal" as used herein includes transition metals. At least a portion of the oxyanions in the coating, preferably the total amount of oxyanions, is present as a mixed oxide (e.g., a ternary oxide) of lithium and one or more elements from the group consisting of metals and metalloids other than Li. In such coatings C2), the oxyanions may be derived from one or more compounds of formula (II) as defined above, wherein d>0, preferably d≥0.02. Therefore, such coatings C2) comprising the oxyanions are obtainable by oxidation of compounds of formula (II) as defined above, wherein d>0, preferably d≥0.02. Therefore, compounds of formula (II) as defined above, wherein d>0, preferably d≥0.02, may be used as precursors of coatings C2) comprising oxyanions.
[0157] In the coated particulate material as described herein, the coating C2) is disposed on the surface of at least a portion of the core particles C1), preferably the coating C2) is disposed on the surface of >50% of the total number of core particles C1), more preferably disposed on the surface of ≥75% of the total number of core particles C1), even more preferably disposed on the surface of ≥90% of the total number of core particles C1) and even more preferably disposed on the surface of ≥95% of the total number of core particles C1) present in the coated particulate material. For the purposes of the present disclosure, the portion of the core particle C1) on which the coating C2) is disposed can be determined by low energy ion scattering (LEIS) or electron microscopy performed on a (representative) sample of the coated particulate material. LEIS gives a reliable quantitative determination of the coating coverage, even when the coating is not visible by SEM.
[0158] In the coated particulate material as described herein, the coating C2) is disposed on at least a portion of the surface of the (individual) core particle C1), preferably the coating C2) is disposed on >50% of the total surface of the core particle C1), more preferably disposed on ≥75% of the total surface of the core particle C1 and even more preferably disposed on ≥90% of the total surface of the core particle C1. For the purposes of the present disclosure, the portion of the surface of the core particle C1) on which the coating C2) is disposed can be determined by low energy ion scattering (LEIS) or electron microscopy performed on a (representative) sample of the (individual) coated particles of the coated particulate material or a (representative) sample of the coated particulate material.
[0159] The coated particulate material as disclosed herein may include a plurality of secondary particles, each secondary particle including a plurality of primary particles in the form of a core (C1), wherein the plurality of primary particles are surrounded by a coating (C2). The surfaces of individual primary particles within such secondary particles may not have a coating because, in the method for preparing a coated particulate material according to the second aspect described herein (see below for details), such primary particles encapsulated within the secondary particles are not in contact with the compound of formula (II) as defined above. In contrast, in the secondary particles of the cathode active material described by Xie et al. (Electrochimica Acta [Electrochemical Journal] 379 (2021) 138124)), substantially all of the primary particles have a sulfur-containing coating on their surface, even when agglomerated within the secondary particles (see Scheme 1 of Electrochimica Acta [Electrochemical Journal] 379 (2021) 138124). This is due to the fact that by involving in Li 2 The cathode active material particles were prepared by a sol-gel method in which the cathode active material particles were formed in situ in the presence of S.
[0160] According to a second aspect, there is provided a method for preparing a coated particulate material according to the first aspect as described above. The method comprises the following steps
[0161] P1) preparing or providing a plurality of core particles C1) as defined above,
[0162] P2) preparing or providing one or more compounds of formula (II) as defined above,
[0163] P3) contacting the materials prepared or provided in steps P1) and P2) with each other, so that a coated particle precursor material is produced, the coated particle precursor material comprising
[0164] CP1) a plurality of core particles C1) as defined above
[0165] as well as
[0166] CP2) a coating provided on the surface of the core particles, the coating comprising one or more compounds of formula (II) as defined above
[0167] P4) heat treating the coated particle precursor material resulting from step P3) at a temperature in the range from 100°C to 700°C under an oxidizing atmosphere so as to produce a coated particle material according to the first aspect defined above.
[0168] It should be understood that the method according to the second aspect as described herein is not a sol-gel method as described by Xie et al. (Electrochimica Acta [Electrochemical Journal] 379 (2021) 138124). Unlike the method described by Xie et al., the method according to the second aspect as described herein does not involve substantial bulk modification of the cathode active material, and produces a coated particulate material having a structure different from the sulfur-modified NCA cathode active material disclosed by Xie et al. (see above). Under the conditions of the method according to the second aspect as described herein, substantially no sulfur diffuses into the core particles C1). This can be verified by SEM-EDX (scanning electron microscopy combined with energy dispersive X-ray spectrometer for coated particulate materials) or by TEM-EDX (transmission electron microscopy combined with energy dispersive X-ray spectrometer for coated particulate materials). Here, SEM-EDX or TEM-EDX means obtaining a cross section from a coated particle identified by SEM or TEM by a focused ion beam, and determining the sulfur concentration in the exposed core by EDX. It was found that the sulfur concentration in the exposed core was close to the detection limit.
[0169] Preferably, in the core particle C1) of the coated particulate material obtained by the method according to the second aspect disclosed herein, the concentration of sulfur is 10% or less, preferably 1% or less, most preferably 0.1% or less of the concentration of sulfur in the coating C2).
[0170] Methods for preparing core particles C1) comprising at least one cathode active material (step P1)), preferably core particles C1) consisting of at least one cathode active material, are known in the art. Core particles C1) comprising at least one cathode active material or consisting of at least one cathode active material are commercially available. Regarding preferred and specific cathode active materials, reference is made to the disclosure provided above in the context of the coated particulate material according to the first aspect. In order to reduce the amount of residual surface carbonates, step P1) may include heat treatment of the core particles C1). The heat treatment of the core particles C1) may be carried out at a temperature in the range of from 700°C to 800°C. The heat treatment of the core particles C1) may be carried out in the presence of an oxygen flow.
[0171] Methods for preparing compounds of formula (II) as defined above (step P2)) are known in the art. With regard to preferred and specific compounds of formula (II), reference is made to the disclosure provided above in the context of the coated particulate material according to the first aspect. Thus, the compound of formula (II) as prepared or provided in step P2) is preferably selected from the group consisting of:
[0172] Lithium sulfide,
[0173] Halogenated lithium sulfide,
[0174] Lithium thiophosphate,
[0175] Lithium halothiophosphate,
[0176] Lithium sulfide modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids other than Li
[0177] a halogenated lithium sulfide modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids different from Li,
[0178] Lithium thiophosphate modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids other than Li
[0179] and a halogenated lithium thiophosphate modified with a sulfide of one or more elements Q selected from the group consisting of metals and metalloids other than Li.
[0180] When the compound of formula (II) is lithium sulfide, a=1 and b=c=d=0.
[0181] In certain cases it is preferred that the compound of formula (II) is not lithium sulfide.
[0182] When the compound of formula (II) is selected from the group consisting of lithium halogenated sulfides, b=d=0 and a+c=1.
[0183] When the compound of formula (II) is selected from the group consisting of lithium thiophosphate, c=d=0 and a+b=1.
[0184] When the compound of formula (II) is selected from the group consisting of lithium halothiophosphates, d=0 and a+b+c=1.
[0185] When the compound of formula (II) is chosen from the group consisting of lithium sulfides modified with sulfides of one or more elements Q chosen from the group consisting of metals different from Li and metalloids, b=c=0 and a+d=1.
[0186] When the compound of formula (II) is chosen from the group consisting of lithium halogenated sulfides modified with sulfides of one or more elements Q chosen from the group consisting of metals different from Li and metalloids, b=0 and a+c+d=1.
[0187] When the compound of formula (II) is selected from the group consisting of lithium thiophosphates modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids different from Li, c=0 and a+b+d=1.
[0188] When the compound of formula (II) is selected from the group consisting of lithium halothiophosphates modified with sulfides of one or more elements Q selected from the group consisting of metals and metalloids different from Li, a+b+c+d=1.
[0189] Preferred compounds of formula (II) are those selected from the group consisting of thiophosphates and halothiophosphates.
[0190] The 2 CO 3 、Lithium oxide Li 2 O, lithium hydroxide LiOH, lithium peroxide Li 2 O 2 One or more materials from the group consisting of anode and cathode active materials and lithium ternary oxides are blended with one or more compounds of formula (II) provided in step P2) to increase the amount of lithium cations and oxygen anions in coating C2), thereby preventing damage to the cathode active material and facilitating sufficient lithium ion conductivity of coating C2).
[0191] The one or more compounds of formula (II) prepared or provided in step P2) may be in the form of a powder, a slurry or a solution.
[0192] In step P3), contacting the materials prepared or provided in steps P1) and P2) may comprise mixing the materials.
[0193] Preferably, the core particles C1) and the compound of formula (II) are mixed in a mass ratio ranging from 10:1 to 12000:1, preferably from 40:1 to 170:1.
[0194] For example, mixing comprises dry powder ball milling or high shear mixing of the core particles C1) with one or more compounds of formula (II) such that the coated particle precursor material comprising:
[0195] CP1) a plurality of core particles C1) as defined above
[0196] as well as
[0197] CP2) A coating provided on the surface of the core particles, the coating comprising one or more compounds of formula (II) as defined above.
[0198] In such cases, it is preferred that in step P1), a plurality of core particles C1) having a particle size in the range from 100 nm to 10 μm as determined by SEM are provided, and in step P2), a dry powder having a particle size in the range from 10 nm to 1 μm as determined by SEM is provided, wherein the size ratio between the core particles C1) and the dry powder provided in step P2) is in the range from 0.1 to 100.
[0199] For example, mixing includes spraying a slurry or solution of one or more compounds of formula (II) onto the core particles C1), or mixing the core particles C1) with a slurry or solution of one or more compounds of formula (II). Subsequently, the solvent of the solution or the carrier liquid of the slurry is evaporated to produce the coated particle precursor material comprising:
[0200] CP1) a plurality of core particles C1) as defined above
[0201] as well as
[0202] CP2) A coating provided on the surface of the core particles, the coating comprising one or more compounds of formula (II) as defined above.
[0203] In step P4), the oxygen-related degradation reaction of the compound of formula (II) is achieved by heat treatment in an oxygen-rich atmosphere. In this way, the compound of formula (II) is degraded on the surface of the cathode active material by oxygen provided from an external source, i.e., without damaging the cathode active material by releasing oxygen from the lattice of the cathode active material.
[0204] In step P4), the heat treatment of the coated particle precursor material produced by step P3) is carried out in an oxidizing atmosphere at a temperature ranging from 100° C. to 700° C., preferably at a temperature ranging from 100° C. to 350° C., in the presence of an oxygen flow or an air flow. The coated particle precursor material produced by step P3) may be pressed into pellets, which are heat treated in step P4).
[0205] In a third aspect, the present invention also relates to a coated particulate material obtainable by the method for preparing a coated particulate material according to the second aspect defined above.
[0206] According to a fourth aspect, an electrode for an electrochemical cell, in particular an all-solid-state lithium-ion electrochemical cell, is provided. The electrode comprises
[0207] E1) a coated particulate material according to the first aspect as defined above, the total amount of which is preferably from 50% to 99% by mass, more preferably from 70% to 97% by mass, relative to the total mass of the electrode,
[0208] E2) a lithium ion-conducting electrolyte material, the total amount of which is preferably from 1% to 50% by mass, more preferably from 3% to 30% by mass, relative to the total mass of the electrode,
[0209] E3) optionally electron-conducting carbon, preferably selected from the group consisting of carbon nanofibers, carbon nanotubes, graphene, carbon black, acetylene black, and coke,
[0210] E4) Optionally one or more binders.
[0211] In the electrode according to the fourth aspect, the coated particulate material E1) according to the first aspect as disclosed above or provided by the method according to the second aspect as disclosed above and the electrolyte material E2) and optionally further ingredients E3) and E4) as defined above may be blended with each other.
[0212] The disclosures provided above in the context of the first and second aspects regarding coated particulate materials apply mutatis mutandis to the electrode according to the fourth aspect. With regard to preferred and specific coated particulate materials, reference is made to the disclosures provided above in the context of coated particulate materials according to the first aspect.
[0213] Typically, the electrode according to the fourth aspect as described herein is a cathode, ie the electrode of the electrochemical cell that produces a net positive charge when the cell is discharged.
[0214] In the electrode according to the fourth aspect described herein, the coating C2) serves the purpose of promoting the transfer of lithium ions between (i) the cathode active material (which is present in the core C1) of the coated particle material) and (ii) the solid electrolyte E2). In addition, the coating C2) acts as a protective layer to protect the solid electrolyte E2) from being oxidized by the cathode active material.
[0215] Suitable solid electrolyte materials capable of conducting lithium ions are known in the art. For example, the solid electrolyte E2) may be selected from the group consisting of lithium-containing sulfides, lithium-containing oxygen sulfides, lithium-containing oxygen phosphates, lithium-containing thiophosphates, lithium argyrodite, lithium-containing halosulfides, and lithium-containing halothiophosphates. In this article, the term "lithium-containing" means that lithium cations are present in the compound forming the electrolyte, but cations of other metals besides lithium may also be present in the compound forming the solid electrolyte.
[0216] Such solid electrolytes have excellent lithium ion conductivity, but may be easily oxidized by the cathode active material, especially in the case of cathode active materials of the 4 V category. In the electrode according to the fourth aspect, the coating C2) acts as a protective layer, protecting the solid electrolyte E2) from oxidation by the cathode active material present in the core C1) of the coated granular material E1).
[0217] In the electrode according to the fourth aspect as defined herein, the coated particulate material E1) and the solid electrolyte material E2) provided according to the first aspect as disclosed above or by the method according to the second aspect as disclosed above can be blended with each other, as well as with one or more electronically conductive materials E3) and / or with one or more adhesives E4). Typical electronically conductive materials E3) are materials containing or consisting of elemental carbon, such as carbon nanofibers, carbon nanotubes, graphene, carbon black, acetylene black, coke and graphene oxide. Typical adhesives are poly(vinylidene fluoride) (PVDF), styrene-butadiene rubber (SBR), polyisobutylene, poly(ethylene vinyl acetate) and poly(acrylonitrile butadiene).
[0218] The electrode according to the fourth aspect as defined herein may comprise a total amount of from 50% to 99%, more preferably from 70% to 97%, of coated particulate material according to the first aspect as disclosed above or provided by the method according to the second aspect as disclosed above, relative to the total mass of the electrode without the current collector.
[0219] The electrode according to the fourth aspect as defined herein may comprise a total amount of solid electrolyte of from 1% to 50%, more preferably from 3% to 30%, relative to the total mass of the electrode without the current collector.
[0220] Optionally, the electrode according to the fourth aspect as defined herein may comprise an electron conducting material comprising or consisting of elemental carbon in a total amount from 0% to 5%, more preferably from 0% to 1%, relative to the total mass of the electrode without the current collector.
[0221] Optionally, the electrode according to the fourth aspect as defined herein may comprise a binder in a total amount of from 0.1% to 3% relative to the total mass of the electrode without the current collector.
[0222] Preferred electrodes according to the fourth aspect as defined herein are those having one or more of the specific and preferred features disclosed herein.
[0223] The present invention also relates to a method for preparing an electrode according to the fourth aspect as described above. The method comprises the following steps:
[0224] M1) providing at least one coated particulate material according to the first aspect or obtained by the method according to the second aspect. E1)
[0225] M2) providing at least one solid electrolyte material E2)
[0226] M3) optionally provides one or both of the additional ingredients E3) and E4) as defined above
[0227] M4) mechanically mixing the components provided in steps M1) to M3) with one another, optionally adding a solvent or a carrier liquid,
[0228] M5) compressing the mixed components obtained in step M4) under a pressure higher than atmospheric pressure, or coating the mixture obtained in step M4) on a current collector, and then removing the solvent or carrier liquid as needed to produce an electrode.
[0229] The disclosures provided above in the context of the first and second aspects regarding the coated particulate material and regarding the electrode according to the fourth aspect apply mutatis mutandis. With regard to preferred and specific coated particulate materials, reference is made to the disclosures provided above in the context of the coated particulate material according to the first aspect. With regard to preferred and specific electrode components E2), E3) and E4), reference is made to the disclosures provided above in the context of the electrode according to the fourth aspect.
[0230] In step M4), a composite material comprising the electrode components E1) and E2, and optionally one or both of E3) and E4), and optionally a solvent can be prepared by mechanical mixing, for example by means of a planetary mill or a ball mill.
[0231] In step M5) of the method for preparing an electrode, the pressure above atmospheric pressure is preferably a pressure in the range from 1 to 450 MPa, more preferably from 50 to 450 MPa and still more preferably from 75 to 400 MPa.
[0232] The invention also relates to an electrode obtainable by a method according to the fourth aspect as described above.
[0233] The present invention also relates to the use of a coated particulate material according to the first aspect or prepared by a method according to the second aspect for preparing an electrode according to the fourth aspect as defined above. The disclosures provided above in the context of the first and second aspects regarding the coated particulate material and regarding the electrode according to the fourth aspect apply mutatis mutandis. With regard to preferred and specific coated particulate materials, reference is made to the disclosures provided above in the context of the coated particulate material according to the first aspect.
[0234] According to another aspect, there is provided an electrochemical cell comprising a coated particulate material according to the first aspect as disclosed above or provided by a method according to the second aspect as disclosed above.
[0235] In the battery cell, preferably, the coated particulate material may be present in the electrode, especially the cathode, according to the fourth aspect as disclosed above.
[0236] The electrochemical cell defined above may be a rechargeable electrochemical cell comprising the following components:
[0237] α) at least one anode,
[0238] β) at least one cathode,
[0239] γ) at least one diaphragm.
[0240] The electrochemical cell described herein may be a cell containing alkali metals, in particular a cell containing lithium ions. In a cell containing lithium ions, charge transport is controlled by Li + Ion influence. In the diaphragm, such electrochemical cells may include a solid electrolyte selected from the group consisting of lithium-containing sulfides, lithium-containing oxygen sulfides, lithium-containing oxygen phosphates, lithium-containing thiophosphates, lithium argyrodite, lithium-containing halogenated sulfides, lithium-containing halogenated thiophosphates, lithium transition metal halides, and lithium-containing phosphorus oxynitrides. Preferably, the solid electrolyte of the diaphragm has the same composition as the solid electrolyte E2) in the electrode, so that the diversity of materials present in the cell is reduced, thereby reducing the complexity of the cell and eliminating undesirable interactions between different materials present in the cell. In addition, the presence of the same material in the solid electrolyte E2) and the diaphragm creates favorable conditions for the transfer of lithium ions between the electrode and the solid electrolyte in the diaphragm.
[0241] Suitable separator materials, electrochemically active cathode materials (cathode active materials) and suitable electrochemically active anode materials (anode active materials) are known in the art. Exemplary cathode active materials are disclosed above in the context of the first aspect. Anode active materials are capable of reversibly plating and stripping lithium metal or deintercalating and intercalating lithium ions. In an electrochemical cell as described herein, the anode α) may comprise graphite carbon, lithium metal or a metal alloy comprising lithium as an anode active material.
[0242] The electrochemical cell may be an all-solid-state electrochemical cell.
[0243] In some cases, the electrochemical cell according to the present invention comprises
[0244] - a cathode which is an electrode according to the fourth aspect as described above
[0245] - a separator layer comprising a solid electrolyte selected from the group consisting of lithium-containing sulfides, lithium-containing oxygen-sulfides, lithium-containing oxygen-phosphates, lithium-containing thiophosphates, lithium-containing argyrodite, lithium-containing halosulfides, lithium-containing halothiophosphates, lithium transition metal halides, and lithium-containing phosphorus oxynitrides,
[0246] - an anode comprising an anode active material capable of reversibly plating and stripping lithium metal or deintercalating and intercalating lithium ions.
[0247] In the electrochemical cell, the coating C2) present in the coated granular material according to the first aspect defined above or obtained by the method according to the second aspect defined above separates the cathode active material from the separator layer that conducts lithium ions. Since the cathode active material in the core C1) is coated with the coating C2) as described in the first aspect defined above or obtained by the method according to the second aspect defined above, direct contact between the cathode active material and the separator layer that conducts lithium ions is prevented. This effect can be verified by analyzing the cathode before and after 100 charge / discharge cycles, for example by time-of-flight mass spectrometry (ToF-SIMS, see the Examples section for details). In a cathode comprising a coated granular material according to the present invention, the increase in the amount of oxidized sulfur and phosphorus species after 100 charge / discharge cycles is significantly lower than a cathode having the same composition except that the coating C2) is absent.
[0248] Thus, coating the cathode active material in the core C1) with a coating C2) as described in the first aspect defined above or obtained by a method according to the second aspect defined above allows the implementation of electrochemical cells, in particular all-solid-state lithium-ion batteries, in which the cathode active material in the core C1) is coated with a coating C2) as described in the first aspect defined above or obtained by a method according to the second aspect defined above. + / Li cathode active material having a redox potential of 4 V or higher and a solid electrolyte E2) and / or a separator layer comprising or consisting of a material that conducts lithium ions, the material itself being in a state of ... + / Li 4V or higher redox potential does not show oxidation stability, such as sulfide-based, thiophosphate-based or oxysulfide-based solid electrolytes. Such materials that conduct lithium ions without high oxidation stability generally show one or more favorable properties, such as stability in the presence of lithium metal or a metal alloy containing lithium, easy processability, excellent ionic conductivity and low cost, which makes them suitable for forming solid electrolytes E2) or diaphragm layers. Therefore, when oxidation stability is not a problem, solid electrolytes E2) or diaphragm layers can be appropriately selected according to the standards of stability, ionic conductivity, processability and cost in the presence of lithium metal or a metal alloy containing lithium.
[0249] The electrochemical cell may have a disc-like or prismatic shape.The electrochemical cell may include a casing which may be made of steel or aluminum.
[0250] A plurality of electrochemical cells as described above can be combined into an all-solid-state battery having both a solid electrode and a solid electrolyte. Another aspect of the present disclosure relates to a battery, more specifically to an alkali metal ion battery, in particular to a lithium ion battery, comprising at least one electrochemical cell as described above, such as two or more electrochemical cells as described above. The electrochemical cells as described above can be combined with each other in an alkali metal ion battery, such as connected in series or in parallel. Series connection is preferred.
[0251] The electrochemical cells or batteries described herein can be used to manufacture or operate automobiles, computers, personal digital assistants, mobile phones, watches, camcorders, digital cameras, thermometers, calculators, laptop BIOS, communication devices or remote car locks, as well as fixed applications, such as energy storage devices for power plants. Another aspect of the invention is a method of manufacturing or operating automobiles, computers, personal digital assistants, mobile phones, watches, camcorders, digital cameras, thermometers, calculators, laptop BIOS, communication devices, remote car locks, and fixed applications (such as energy storage devices for power plants) by using at least one battery of the invention or at least one electrochemical cell of the invention.
[0252] Another aspect of the present disclosure is the use of an electrochemical cell as described above in a motor vehicle, a bicycle operated by an electric motor, a robot, an aircraft (such as an unmanned aerial vehicle, including a drone), a ship or a stationary energy storage.
[0253] The present disclosure further provides a device comprising at least one electrochemical cell of the present invention as described above. Preferably it is a mobile device, such as a vehicle, for example a car, a bicycle, an aircraft or a water vehicle such as a boat or a ship. Other examples of mobile devices are portable mobile devices, such as computers, especially laptop computers, telephones or power tools, for example from the construction industry, especially drills, battery-powered screwdrivers or battery-powered nailers.
[0254] The present invention is further illustrated by the following non-limiting examples.
[0255] Examples
[0256] Preparation of coated particulate materials
[0257] A first coated particulate material is prepared by a method, the first coated particulate material comprising
[0258] C1) a plurality of core particles, each core particle comprising a cathode active material LiNi 0.85 Co 0.1 Mn 0.05 O 2 (NCM851005, commercially available)
[0259] C2) contains Li 3 PS 4 (a thiophosphate compound of formula (II) wherein a=0.75, b=0.25, c=d=0, commercially available) is coated with an oxidation product,
[0260] and a second coated particulate material comprising
[0261] C1) a plurality of core particles, each core particle comprising a cathode active material LiNi 0.85 Co 0.1 Mn 0.05 O 2 (NCM851005)
[0262] C2) contains Li 6 PS 5 (a thiophosphate compound of formula (II) wherein a=0.625, b=0.125, c=0.25, d=0; commercially available) coating of an oxidation product,
[0263] The method comprises the following steps:
[0264] P1) provides a plurality of core particles C1) comprising a cathode active material LiNi 0.85 Co 0.1 Mn 0.05 O2 (NCM851005, commercially available)
[0265] P2) Provide Li 3 PS 4 or Li 6 PS 5 Cl powder
[0266] The mass ratio between the core particles C1) provided in step P1 and the powder provided in step P2) is 99:1
[0267] P3) Mixing the materials prepared or provided in steps P1) and P2) with one another for 30 minutes, so that a coated particle precursor material is produced, the coated particle precursor material comprising
[0268] CP1) a plurality of core particles C1), each core particle comprising a cathode active material LiNi 0.85 Co 0.1 Mn 0.05 O 2
[0269] as well as
[0270] CP2) a coating layer disposed on the surface of these core particles, the coating layer comprising Li 3 PS 4 or Li 6 PS 5 Cl
[0271] P4) Pressing the coated particle precursor material obtained in step P3) into pellets and heat treating the pellets at 300° C. for 1 hour in air so as to produce the first coated particle material defined above or the second coated particle material defined above.
[0272] Characterization of morphology
[0273] Each coated particle material was studied using scanning electron microscopy (SEM) to determine the changes in surface morphology due to the coating.
[0274] Figure 1 SEM micrographs of the following samples are shown:
[0275] - Bare core particle C1)( Figure 1 a, 1d)
[0276] - a first coated particulate material ( Figure 1 b. 1e)
[0277] - Second coated particulate material ( Figure 1 c. 1f)
[0278] And the following STEM low-angle annular dark field (LAADF) image of the sample:
[0279] - Bare core particle C1)( Figure 1 g)
[0280] - a first coated particulate material ( Figure 1 h)
[0281] - Second coated particulate material ( Figure 1 i).
[0282] exist Figure 1 In a, 1b, and 1c, the magnification scale is 200 nm. Figure 1 In d, 1e, and 1f, the length of the magnification scale is 1 μm.
[0283] Figure 1 The arrows in h) or 1i) indicate the coating on the core particle C1) of the first coated particulate material or the second coated particulate material.
[0284] Compared to the bare core particles C1), the sample of the first coated particle material shows blurred grain boundaries and a flattened overall surface of the core particles C1). Apparently, the core particles C1) comprising the cathode active material are encapsulated by the coating C2), resulting in the formation of secondary particles having a flattened surface and comprising a plurality of core particles C1) surrounded by the coating C2). For the second coated particle material, small flakes can be observed on the particle surface, and the grain boundaries between the core particles C1) appear to be less blurred. Compared to the second coated particle material, the coating C2) appears thicker and more evenly distributed in the first coated particle material.
[0285] As shown in the STEM image, the bare core particle C1) exhibits a smooth surface ( Figure 1 g), while the first coated particle material exhibits a coating ( Figure 1 h), and the second coated particulate material exhibits a thinner coating ( Figure 1 i).
[0286] Overall, SEM and STEM investigations confirmed that in each case a coated particulate material as defined above was obtained.
[0287] Characterization of coating compositions
[0288] In order to determine the chemical composition of the coatings, X-ray photoelectron spectroscopy (XPS) analysis was performed.
[0289] Figure 2 Details of the XP spectra (binding energy range is S2p, P 2p, Cl 2p, C 1s, O 1s and Li 1s) of the following samples are shown:
[0290] - bare core particle C1) (uppermost spectrum in each case)
[0291] - First coated particulate material (lowermost spectrum in each case)
[0292] - Second coated particulate material (in each case middle spectrum).
[0293] Overall, the XP detail spectra indicate that the surface composition of the coated samples is mainly sulfate (most likely Li 2 SO 4 ), phosphate (most likely Li 3 PO 4 ) and carbonates (most likely Li 2 CO 3 ). For the samples of bare core particles C1), the carbonate fraction is higher compared to the samples of coated particle material.
[0294] For the samples of bare core particles C1) (uppermost spectrum in each case), the XP spectrum shows a LiNi 0.85 Co 0.1 Mn 0.05 O 2 signal (denoted as “3) NCM”) and can be assigned to carbonates (most likely Li 2 CO 3 ) (denoted as “1) carbonate” or “2) carbonate”). In addition, relatively weak signals can be observed in the binding energy range of sulfate, which is most likely due to the presence of LiNi 0.85 Co 0.1 Mn 0.05 O 2 Synthetic Li 2 SO 4 Such contaminants were reported by Ahmed et al. (ACS Nano 2019, 13(9), 10694-10704, https: / / doi.org / 10.1021 / acsnano.9b05047) and designated as Li-containing 2 SO 4 Nanopores within the particles.
[0295] For the first sample of coated particulate material (lowermost spectrum in each case), the XP spectrum shows salts attributable to sulfate and phosphate (most likely Li 2 SO 4 and Li 3 PO 4 The ratio between P 2p and S2p signals is about 1:4, which is consistent with the precursor Li 3 PS4 This indicates that Li 3 PS 4 The conversion to sulfate and phosphate (most likely Li 2 SO 4 and Li 3 PO 4 In addition, it can be seen that the 2 CO 3 However, the fraction of carbonate is much smaller than that of the sample of bare core particle C1), indicating that the coating is formed on the Li-rich core particle C1). 2 CO 3 On the surface (note that XPS is a surface sensitive technique) or Li 2 CO 3 Participates in the reaction occurring during the heat treatment in step P4) and is consumed. 0.85 Co 0.1 Mn 0.05 O 2 The signal of almost disappears in the first coated particulate material, so the coating appears to be highly covered and / or relatively thick. Assuming that during step P4), Li 3 PS 4 Reacts with oxygen to form Li 2 SO 4 and Li 3 PO 4 , an additional Li source must be included because in the obtained product as a whole (a molar ratio of 4:1 Li 2 SO 4 +Li 3 PO 4 ), the ratio of Li:(S+P) is 11:5, which is higher than Li 3 PS 4 (3:5). Without wishing to be bound by any theory, it is conceivable that LiNi 0.85 Co 0.1 Mn 0.05 O 2 and / or Li 2 CO 3 Act as a source of inspiration.
[0296] For the sample of the second coated particulate material (the middle spectrum in each case), the XP spectrum shows S 2p and P 2p signals at the same binding energy positions as in the XP spectrum of the sample of the first coated particulate material, indicating that sulfate and phosphate (most likely Li 2 SO 4 and Li 3 PO4 ). It is noteworthy that the ratio between P 2p and S2p signals is about 1:25, which is far from the precursor Li 6 PS 5 The S2p, P, and Cl 2p spectra indicate that the coating formation is accompanied by the loss of P and Cl species, ultimately due to the formation of volatile P- and Cl-containing products. Carbonates (most likely Li 2 CO 3 ) still appears to be present in the uppermost surface region. Designated as LiNi 0.85 Co 0.1 Mn 0.05 O 2 The signal is stronger than that of the sample with the first coated particle material, so the coating appears to be less covered and / or thinner for the second coated particle material. This finding is consistent with the SEM results (see Figure 1 ) are consistent.
[0297] Effect of coating on electronic conductivity
[0298] To determine the electronic conductivity, a sample of the cathode active material to be investigated (bare core particle C1, first coated particle material or second coated particle material) was placed between two steel die current collectors. The chronoamperometry technique was used at a polarization voltage of 100 mV for 300 s. During this time, the current was essentially constant. The electronic conductivity of the sample of bare core particle C1) was 22.7 mS cm -1 In contrast, the samples of the first coated particulate material and the second coated particulate material exhibited 10.7 mS cm -1 and 3.8 mS cm -1 These results indicate that the coating hinders the electron transport through the cathode active material. However, while low electronic conductivity may limit the performance of the battery (i.e., power density) on the one hand, on the other hand, a coating with low electronic conductivity is beneficial in mitigating interfacial degradation and self-discharge.
[0299] Effect of coating on battery performance
[0300] The constant current charge / discharge measurements were performed using a VMP300 electrochemical workstation (Biologic Science Instrument SAS) and a MACCOR potentiostat / galvanostat. The Biologic VMP 300 potentiostat was used for impedance measurements over cycles. The cells were operated at 0.2C (about 0.39 mA cm) in a voltage range of 2 to 3.7 V relative to In / InLi. -2 , 1C = 180mA (g cathode active material) -1 ) at a C rate of 1.7V relative to In / InLi. Impedance measurements were performed after charging to 3.7V relative to In / InLi. The impedance spectrum was measured by applying a 10mV amplitude at 10 points per decade in the frequency range of 1MHz-0.1Hz. The cells were cycled at a C rate of 0.2C in a voltage range of 2 to 3.9V relative to In / InLi using a MACCOR constant current instrument. The dQ / dV graphs were obtained from the charge / discharge curves. All electrochemical measurements were performed in a climate chamber at 25°C.
[0301] Galvanostatic charge / discharge tests were performed to characterize the effect of coating C2) on the electrochemical performance.
[0302] These cells have the following configurations
[0303] In / InLi|Li 5.5 PS 4.5 Cl 1.5 |Bare LiNi 0.85 Co 0.10 Mn 0.05 O 2 or the first coated particulate material or the second coated particulate material / Li as defined above 5.5 PS 4.5 Cl 1.5 .
[0304] In the cathode of the battery cell, the cathode active material (bare LiNi 0.85 Co 0.10 Mn 0.05 O 2 or the first coated particulate material or the second coated particulate material as defined above) and Li 5.5 PS 4.5 Cl 1.5 The mixture was mixed in a ratio of 7:3. No carbon additives or binders were used. To achieve a homogeneous composite cathode, the mixture was hand ground using an agate mortar for 30 minutes.
[0305] All cells were placed in an argon-filled glove box (p (O2) / p<0.1ppm and p (H2O) / p<0.1ppm; MBRAUN Labmaster SP). For assembly, a homemade pellet-type cell case with a 10 mm diameter PEEK sleeve and two stainless steel dies was used. First, 60 mg Li 5.5 PS 4.5 Cl 1.5 To obtain a diaphragm. About 12mg cathode composite material is added to one side of the obtained diaphragm and evenly distributed to form stacked pellets. Afterwards, the stacked pellets are pressed for 3 minutes at 3 tons (about 380MPa). Indium foil (Alfa Aesar, 99.99%, 8mm diameter, 100μm thickness) and lithium foil (Albemarle, Rockwood Lithium GmbH, 99.9%, 4mm diameter, 100μm thickness) are added to the other side of the diaphragm to form In / InLi anode. The battery core is fixed by an aluminum frame to maintain a constant pressure (about 70MPa).
[0306] The cells were heated at 25°C at 2 to 3.7 V ( Figure 3a ) or 2 to 3.9V relative to In / InLi ( Figure 3b ) within the voltage range of 0.2C (about 0.39mAcm -2 )Next cycle. Figure 3a and 3b The development of the discharge capacity as a function of the number of cycles is shown.
[0307] The initial discharge capacity of cells with cathodes containing one of these coated particle materials was comparable to that of cells with cathodes containing bare LiNi 0.85 Co 0.10 Mn 0.05 O 2 Without wishing to be bound by any theory, it is currently assumed that this is due to the reduced electronic conductivity in the cathode caused by the electrically insulating coating (C2). This assumption can also explain why the cells with cathodes comprising the first coated granular material show a lower initial discharge capacity than the cells with cathodes comprising the second coated granular material. As derived from SEM and XPS studies (see above), the coating (C2) of the second coated granular material may be thinner than the coating (C2) of the first coated granular material.
[0308] However, during cycling, the capacity loss of the cells having a cathode comprising one of these coated particulate materials was significantly reduced compared to the reference cells. Thus, the cells having a cathode comprising the first coated particulate material and the cells having a cathode comprising the second coated particulate material showed much higher capacity retention after 100 cycles, namely 85% and 86%, respectively ( Figure 3a The reference cell (the cathode containing bare core particles C1) exhibited 194.3 mAh (g cathode active material) -1 However, after 100 cycles, the capacity decreased to 106.1 mAh (g cathode active material). -1 , corresponding to a capacity retention of 55%. In contrast, the cell having a cathode comprising the first coated particulate material exhibited 163.2 mAh (g cathode active material) -1 The initial discharge capacity and 139.3 mAh (g cathode active material) after 100 cycles -1 The cell with a cathode containing the second coated particulate material showed 175.3 mAh (g cathode active material) -1 The initial discharge capacity and 149.8 mAh (g cathode active material) after 100 cycles -1 , corresponding to a capacity retention of 85%.
[0309] Figure 4 a to Figure 4 c presents exemplary galvanostatic charge / discharge curves of the three cells in the voltage range of 2 to 3.7 V vs. In / InLi (1st, 10th and 50th cycles in each case). Figure 4 a to Figure 4 In c, “bare NCM” indicates a reference cell, “LPS-coated NCM” indicates a cell having a cathode comprising a first coated particulate material, and “LPSC-coated NCM” indicates a cell having a cathode comprising a second coated particulate material.
[0310] As the upper cycle voltage increases to 3.9 V ( Figure 3b ), the initial capacity of the reference cell and the cell with a cathode comprising the first coated particulate material increased slightly due to the higher state of charge (SOC). However, the more severe cycling conditions resulted in more severe degradation. Figure 5 Exemplary galvanostatic charge / discharge curves of three cells in the voltage range of 2 to 3.9 V vs. In / InLi are shown in Figs. a to 5c (1st, 10th, 50th and 100th cycle in each case). Figure 5 a to Figure 5In c, "bare NCM" indicates a reference cell, "LPS-coated NCM" indicates a cell with a cathode comprising a first coated granular material, and "LPSC-coated NCM" indicates a cell with a cathode comprising a second coated granular material. After 100 cycles, the cells showed capacity retention rates of 58% (bare core particles C1), 78% (first coated granular material), and 84% (second coated granular material), respectively.
[0311] Overall, the cell cycling tests demonstrated that both coatings (C2) mitigated capacity loss during cycling and thus improved battery performance. The second coated particle material performed slightly better in terms of discharge capacity and capacity retention, which may be attributed to the higher ionic conductivity of the coating and / or the thinner coating.
[0312] To monitor the impedance evolution upon cell cycling, electrochemical impedance spectroscopy (EIS) was collected at 3.7 V vs. In / InLi in the charged (delithiation) state. Figure 4 d to 4f show the Nyquist diagram. Figure 4 d to Figure 4 In f, "bare NCM" indicates a reference cell, "LPS coated NCM" indicates a cell with a cathode comprising a first coated granular material, and "LPSC coated NCM" indicates a cell with a cathode comprising a second coated granular material. After the first charge, the reference cell (cathode comprising bare core particles C1) exhibited the lowest cell impedance, which is consistent with the highest initial discharge capacity. The initial impedance of the cell with a cathode comprising the first coated granular material was significantly higher, while the difference with the cell with a cathode comprising the second coated granular material was less significant. After 50 cycles, the impedance of the reference cell increased significantly compared to the cells with cathodes comprising the first coated granular material or the second coated granular material (where the impedance increase was not much more significant).
[0313] dQ / dV plots of the three cells at the 1st, 10th, 50th and 100th cycles (voltage range 2 to 3.9 V vs. In / InLi in each case) ( Figure 5d to 5f, where "bare NCM" indicates a reference cell, "LPS coated NCM" indicates a cell with a cathode comprising a first coated particulate material, and "LPSC coated NCM" indicates a cell with a cathode comprising a second coated particulate material) show typical redox peaks, indicating a multiphase transformation process of a cathode active material comprising nickel, cobalt, and manganese, including a transformation from a first hexagonal (H1) phase to a monoclinic (M) phase, from an M phase to a second hexagonal (H2) phase, and from an H2 phase to a third hexagonal (H3) phase. The H2-H3 phase transition induces significant volume strain in the Ni-rich cathode active material, which results in contact loss at the interface between the cathode active material and the solid electrolyte. For the first cycle, the cells with cathodes comprising the first coated particulate material or the second coated particulate material exhibit an upward shift in the redox peak potential compared to the reference cell, suggesting that the initial deintercalation process is kinetically hindered by the coating. It should be noted that the cells with cathodes comprising the second coated particulate material showed lower overpotentials than the cells with cathodes comprising the first coated particulate material, which is consistent with the results obtained by electrochemical impedance spectroscopy ( Figure 4 d to 4f). Upon cycling, the shift in the redox potential of the reference cell corresponds to the increased overvoltage caused by increased interfacial degradation. The cells with cathodes comprising the first coated particulate material or the second coated particulate material showed only a small shift in the redox peak compared to the reference cell. This indicates that the coating mitigates interfacial degradation, which is consistent with the results obtained by electrochemical impedance spectroscopy ( Figure 4 df) are consistent.
[0314] In the range from 0.1C to 5C (1C = 1.93 mA cm -2 ) were tested at different C rates to test the fast charging capacity of the cathode active material (bare core particle C1), the first coated particle material or the second coated particle material). The results are shown in Figure 6 a to Figure 6 In d, "bare NCM" indicates a reference cell, "LPS-coated NCM" indicates a cell having a cathode comprising a first coated particulate material, and "LPSC-coated NCM" indicates a cell having a cathode comprising a second coated particulate material. At low C rates (0.1C and 0.2C), the reference cell (cathode comprising bare core particles C1) exhibited a higher discharge capacity than the cell having a cathode comprising the first coated particulate material or the second coated particulate material. As the current density increases, the cell having a cathode comprising the first coated particulate material or the second coated particulate material maintains a higher discharge capacity. Even at a high C rate of 2C, the cell having a cathode comprising the first coated particulate material or the second coated particulate material provides 112 and 107 mAh (g cathode active material), respectively. -1This result implies that the coating in the first coated particulate material and the second coated particulate material alleviates the charge transfer barrier at high current density. In addition, at high C-rates, the capacity of the cell with a cathode comprising the second coated particulate material remains much more stable than that of the cell with a cathode comprising the first coated particulate material, which may be attributed to the slower interfacial degradation due to the lower electronic conductivity of the second coated particulate material.
[0315] Effects of coatings on the interfacial reactions between cathode active materials and thiophosphate-based solid electrolytes
[0316] In order to study the effect of coating C2) on the cathode active material LiNi 0.85 Co 0.10 Mn 0.05 O 2 With solid electrolyte Li 5.5 PS 4.5 Cl 1.5 To investigate the effect of the interfacial reaction between the cathode and the current collector, time-of-flight mass spectrometry (ToF-SIMS) analysis of the cathode was performed before and after the cell cycle. The analysis was performed on the surface of the cathode oriented toward the current collector. At least ten mass spectra were measured in different areas on the surface for each sample to ensure the reproducibility of the results.
[0317] Without wishing to be bound by any theory, it is understood that PO 3 - and SO 3 - The fragmentation can be considered indicative of interfacial reactions involving oxygen of the cathode active material with the thiophosphates or halothiophosphates of the solid electrolyte to oxidized phosphorus and sulfur species.
[0318] Figure 7a and 7b The PO normalized to the respective total ion intensity is shown. 3 - and SO 3 - Signal intensity. Before cycling, the three samples (including bare LiNi 0.85 Co 0.10 Mn 0.05 O 2 The normalized intensities of the cathode comprising the first coated granular material, the cathode comprising the second coated granular material (C2) are almost at the same level, although the coatings (C2) of the first coated granular material and the second coated granular material comprise phosphate and sulfate.
[0319] From the literature (Walther, F. et al., Chem. Mater [Material Chemistry]. 2019, 31(10), 3745-3755. https: / / doi.org / 10.1021 / acs.chemmater.9b00770; Walther, F. et al., Chem. Mater [Material Chemistry]. 2020, 32(14), 6123-6136. https: / / doi.org / 10.1 021 / acs.chemmater.0c01825; Nolan, AM et al., Joule [Journal of Joules] 2018, 2(10), 2016-2046. https: / / doi.org / 10.1016 / j.joule.2018.08.017; Xiao, Y et al., Joule [Journal of Joules] 2019, 3(5), 1252-1275) It is known that thiophosphates and cathode active materials such as LiNi 0.85 Co 0.10 Mn 0.05 O 2 can react with each other just upon contact to form products such as Li 3 PO 4 and Li 2 SO 4 While these reactions are inhibited by coating (C2) in cathodes containing the first coated particulate material or the second coated particulate material, they are not hindered in cathodes containing bare cathode active material, resulting in the formation of a certain amount of PO in the ToF-SIMS data. x - and SO x - Fragments, similar to the ToF-SIMS data for cathodes containing either the first coated particulate material or the second coated particulate material.
[0320] After cell cycling (100 cycles), for all samples, PO 3 - and SO 3 - The intensity in the fragments increases significantly. However, for cathodes containing the first coated particulate material or the second coated particulate material, the signal increase is much smaller. This indicates that the cathode active material LiNi 0.85 Co 0.10 Mn 0.05 O 2 With solid electrolyte Li 5.5 PS 4.5 Cl 1.5The interfacial reaction at the interface between is suppressed by coating C2). This conclusion, in turn, explains the improvement in capacity retention and cell performance. Since the signal intensities of the two coatings C2) are comparable, the two coatings appear to suppress the interfacial reaction to a similar extent.
Claims
1. A coated granular material comprising C1) a plurality of core particles, each core particle comprising one or more compounds of formula (I): Li 1+t [Ni x Co y Mr z M u ] 1-t O2(I) in 0≤x≤1 0≤y≤1 0≤z≤1 0≤u≤0.15 x+y+z>0 x+y+z+u=1 0≤t≤0.2 M, if present, is one or more elements selected from the group consisting of Al, Mg, Ba, B, Mo, Ti, Nb, W, Zr, as well as C2) a coating disposed on the surface of the core particles, the coating comprising - lithium cations, and - oxidized sulfur species, wherein the oxidized sulfur species is an oxidation product of one or more compounds of formula (II) (Li2S) a( P2S5) b (LiX) c (Q 2 / e S) d (II) in X corresponds to one or more selected from the group consisting of F, Cl, Br and I and pseudohalide ions, the pseudohalide selected from N3 - 、SCN - , CN - 、OCN - , BF - and BH - The group composed of Q corresponds to one or more elements selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, e is the oxidation number of Q, 0≤a≤1 0≤b<1, preferably, 0≤b<0.98 0≤c<1, preferably, 0≤c<0.98 0≤d<1, preferably, 0≤d<0.98 a+b+c+d=1 The premise is that when a=0, -c>0, preferably ≥0.02 - and one of b and d > 0, preferably ≥ 0.
02.
2. The coated particulate material according to claim 1, wherein The compound of formula (II) is selected from the group consisting of: Lithium sulfide, Halogenated lithium sulfide, Lithium thiophosphate, Lithium halothiophosphate, Lithium sulfide modified with sulfides of one or more elements Q selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, A halogenated lithium sulfide modified with a sulfide of one or more elements Q selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, A lithium thiophosphate modified with a sulfide of one or more elements Q selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, and a halogenated lithium thiophosphate modified with a sulfide of one or more elements Q selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg.
3. The coated particulate material according to claim 1 or 2, wherein The oxidized sulfur species contain sulfate anions, wherein at least a portion of the sulfate anions in the coating, preferably the total amount of the sulfate anions, are present as lithium sulfate Li2SO4.
4. A coated particulate material according to any preceding claim, wherein The coating further comprises an oxidized phosphorus species, wherein the oxidized phosphorus species is an oxidation product of one or more compounds of formula (II), wherein b>0.
5. The coated particulate material according to claim 4, wherein The oxidized phosphorus species are oxidation products of one or more compounds from the group consisting of: Lithium thiophosphate, Lithium halothiophosphate, Lithium thiophosphates and halogenated lithium thiophosphates modified with a sulfide of an element Q selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg.
6. A coated particulate material according to claim 4 or 5, wherein The oxidized phosphate species contain phosphate anions, wherein at least a portion of the phosphate anions in the coating, preferably the total amount of the phosphate anions, are present as lithium phosphate Li 3 PO 4 .
7. A coated particulate material according to any preceding claim, wherein - the fraction of sulfur ranges from 0.09% to 10.0%, preferably from 0.4% to 4.0%, as measured by inductively coupled plasma optical emission spectroscopy, and / or - the fraction of phosphorus ranges from 0.01% to 10.0%, preferably from 0.05% to 4.0%, as measured by inductively coupled plasma optical emission spectroscopy, In each case relative to the total mass of the plurality of core particles C1) and their coating C2).
8. A coated particulate material according to any preceding claim, wherein The coating contains Li3PO4 and Li2SO4.
9. A coated particulate material according to any preceding claim, wherein The coating further comprises one or more of the following - halogen anions, wherein at least a portion of the halogen anions in the coating, preferably the total amount of the halogen anions, is present as lithium halide, - carbonate anions, wherein at least a portion of the carbonate anions in the coating, preferably the total amount of carbonate ions, is present as lithium carbonate, anions selected from the group consisting of oxygen anions, hydroxide anions and peroxide anions, wherein at least a portion of said anions in the coating, preferably the total amount of said anions, is present as one or more of lithium oxide Li2O, lithium hydroxide LiOH and lithium peroxide Li2O2, - Oxygen-containing anions of elements from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, wherein at least a portion of these oxy-containing anions in the coating, preferably the total amount of the oxy-containing anions, is present as a mixed oxide of lithium and one or more elements from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg.
10. An electrode for a solid-state lithium-ion electrochemical cell and / or an all-solid-state lithium-ion electrochemical cell, the electrode comprising E1) a coated particulate material as defined in any one of claims 1 to 9, the total amount of which is preferably from 50% to 99% by mass, more preferably from 70% to 97% by mass, relative to the total mass of the electrode, E2) a solid electrolyte material that conducts lithium ions, the total amount of which is preferably from 1% to 50% by mass, more preferably from 3% to 30% by mass, relative to the total mass of the electrode, E3) optionally electron-conducting carbon, preferably selected from the group consisting of carbon nanofibers, carbon nanotubes, graphene, carbon black, acetylene black, and coke, E4) Optionally one or more binders.
11. A method for preparing a coated particulate material as defined in any one of claims 1 to 9, the method comprising the steps of: P1) preparing or providing a plurality of core particles C1) as defined in claim 1, P2) preparing or providing one or more compounds of formula (II) as defined in claim 1, P3) contacting the materials prepared or provided in steps P1) and P2) with each other, so that a coated particle precursor material is produced, the coated particle precursor material comprising CP1) a plurality of core particles C1) as defined in claim 1 as well as CP2) a coating provided on the surface of the core particles, the coating comprising one or more compounds of formula (II) as defined in claim 1 P4) heat treating the coated particle precursor material resulting from step P3) at a temperature in the range from 100°C to 700°C under an oxidizing atmosphere, so as to produce a coated particle material as defined in any one of claims 1 to 9.
12. The method according to claim 11, wherein: - the one or more compounds of formula (II) as defined in claim 1 prepared or provided in step P2) are selected from the group consisting of: Lithium sulfide, Halogenated lithium sulfide, Lithium thiophosphate, Lithium halothiophosphate, Lithium sulfide modified with sulfides of one or more elements selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, A halogenated lithium sulfide modified with a sulfide of one or more elements selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, A lithium thiophosphate modified with a sulfide of one or more elements selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, and a halogenated lithium thiophosphate modified with a sulfide of one or more elements selected from the group consisting of B, Al, Si, Ge, Sn, Sb, Zr, Ga, Zn and Mg, and / or - in step P3), contacting the materials prepared or provided in steps P1) and P2) comprises mixing said materials, preferably by - dry powder ball milling or high shear mixing of these core particles C1) with one or more compounds of formula (I) - spraying a slurry or solution of one or more compounds of formula (II) onto the core particles C1 and evaporating the solvent of the solution or the carrier liquid of the slurry - mixing the core particles C1) with a slurry or solution of one or more compounds of formula (II) and evaporating the solvent of the solution or the carrier liquid of the slurry and / or - In step P4), the heat treatment is carried out in the presence of a flow of oxygen or of air.
13. The method according to claim 11 or 12, wherein: One or more materials selected from the group consisting of lithium carbonate Li2CO3, lithium oxide Li2O, lithium hydroxide LiOH, lithium peroxide Li2O2, and lithium ternary oxide admixed with the one or more compounds provided in step P2).
14. An electrochemical cell, comprising - a coated particulate material as defined in any one of claims 1 to 9 or obtained by a process according to any one of claims 11 to 13, or - An electrode as defined in claim 10.
15. Use of a coated particulate material according to any one of claims 1 to 9 or obtained by a process according to any one of claims 11 to 13 for the preparation of an electrode as defined in any one of claims 10 and 11.
Citation Information
Patent Citations
Active material for battery, non-aqueous electrolyte battery and battery pack
US20100015509A1
Coated particulate material comprising complex layered oxide for use as electrode active material, respective methods of making and uses thereof
WO2020249659A1